Significance of Modern Diagnostic Methods of Sepsis - Nuruzova Z.A.; Yodgorova N.T.; Mamanov J.B. (Scholars Digest Publishing, 2023)
In this literature analysis the treatment measures of sepsis in recent years (2012-2022), modern diagnostic methods, the importance of modern serological, molecular-biological, molecular-genetic methods, their possibilities and advantages, and effective treatment methods are widely covered. For example, real-time PCR (Real-Time PCR), immuno-PCR, correlation CMG classifier, component analysis (PCA), Anti-inflammatory therapy, Tumor Necrosis Factor (TNF-a), which are considered one of the new, modern forms of PCR, were conducted in such patients As a result of many clinical trials, several pharmacological agents are highly effective, for example: glucocorticoids, non-steroidal anti-inflammatory drugs, monoclonal antibodies and platelet-activating, immune-enhancing agents.
Keywords: Sepsis, Streptococcus, PZR, correlation CMG classifier, component analysis (PCA), Anti-inflammatory therapy, Tumor Necrosis Factor (TNF-a).